Betaine and secondary events in an acute coronary syndrome cohort. - Michael Lever (PLoS ONE, 2012)
BACKGROUND: Betaine insufficiency is associated with unfavourable vascular risk profiles in metabolic syndrome patients. We investigated associations between betaine insufficiency and secondary events in acute coronary syndrome patients. METHODS: Plasma (531) and urine (415) samples were collected four months after discharge following an acute coronary event. Death (34), secondary acute myocardial infarction (MI) (70) and hospital admission for heart failure (45) events were recorded over a median follow-up of 832 days. PRINCIPAL FINDINGS: The highest and lowest quintiles of urinary betaine excretion associated with risk of heart failure (p = 0.0046, p = 0.013 compared with middle 60%) but not with subsequent acute MI. The lowest quintile of plasma betaine was associated with subsequent acute MI (p = 0.014), and the top quintile plasma betaine with heart failure (p = 0.043), especially in patients with diabetes (p<0.001). Top quintile plasma concentrations of dimethylglycine (betaine metabolite) and top quintile plasma homocysteine both associated with all three outcomes, acute MI (p = 0.004, <0.001), heart failure (p = 0.027, p<0.001) and survival (p<0.001, p<0.001). High homocysteine was associated with high or low betaine excretion in >60% of these subjects (p = 0.017). Median NT-proBNP concentrations were lowest in the middle quintile of plasma betaine concentration (p = 0.002). CONCLUSIONS: Betaine insufficiency indicates increased risk of secondary heart failure and acute MI. Its association with elevated homocysteine may partly explain the disappointing results of folate supplementation. In some patients, especially with diabetes, elevated plasma betaine also indicates increased risk.